Performance of inter-chip RF-interconnect using CPW, capacitive coupler and UWB transceiver - Sun, Mei (2009)
A novel inter-chip RF-interconnect system operating in the range of 22–29 GHz is described and analyzed in terms of system bit error rate (BER) performance. After characterizing the interconnect channel, plotting the transmitted and received ultrawideband pulses, and estimating the switching noise power density by proposing a novel switching noise attack model, we finally get the results of the system performance. It is shown that the performance degrades with the interconnect distance and the switching noise attacker number. It is concluded that a high data rate at 3.33 Gb/s with a low BER less than 10^(-5) over the entire chip of size 30 X 30 mm2 is achievable with the radiated power density less than 41 dBm/MHz (or the average transmitted power less than 2.85 dBm).